Towards a policy relevant neighborhoods and health agenda: engaging citizens, researchers, policy makers and public health professionals. SESPAS Report 2018 - Manuel Franco; Julia Díez; Pedro Gullón; Mario Margolles; Rafael Cofiño; Maribel Pasarín; Carme Borrell (Elsevier, 2018)
A large volume of public health literature has shown how the social and physical features of a neighbourhood affect residents' health, and how they contribute to health inequalities. In this article, we argue that citizens, researchers, policy makers and health professionals should engage in creating a common, policy-relevant neighbourhood and health agenda to effectively improve population health and reduce health inequalities. We discuss four critical processes for advancing this neighbourhood and health agenda: 1) citizen participation and community empowerment; 2) policy making; 3) producing relevant research; and 4) how to best communicate between stakeholders. Various methodologies and experiences currently exist to secure and promote citizen participation. Sufficient funding of research projects and specific policies, as well as continued communication strategies among stakeholders, are necessary elements of this neighbourhood and health agenda. Establishing collaborative and sustained relationships between citizens, policy makers, health professionals and researchers at local and higher political levels is a challenging but necessary step. Developing participatory action research and local participatory policy efforts are important steps towards developing a policy- relevant neighbourhood and health agenda. Resumen: Numerosos ejemplos de la literatura en salud pública han puesto de manifiesto el impacto de las características sociales y físicas del barrio sobre el estado de salud de las personas residentes, así como su influencia sobre las desigualdades en salud. En este artículo de posicionamiento sostenemos que ciudadanía, personas investigadoras, decisoras políticas y profesionales de la salud deberían involucrarse en construir una estrategia común en barrios y salud, que promueva mejorar la salud de la población y que disminuya de manera efectiva las desigualdades en salud. Para ello identificamos y discutimos cuatro procesos críticos necesarios para avanzar en esta agenda de barrios y salud: 1) la participación y el fortalecimiento de la comunidad; 2) la elaboración de políticas locales; 3) la realización de investigaciones relevantes; y 4) la comunicación entre estos agentes. Existen diferentes metodologías y experiencias que fomentan y promueven la participación y el fortalecimiento de la ciudadanía. A su vez, se requiere una financiación suficiente de proyectos de investigación, políticas específicas y la puesta en marcha de estrategias continuas de comunicación. Establecer relaciones colaborativas a largo plazo, tanto de ámbito local como a niveles superiores, entre ciudadanía, decisores/as políticos/as, expertos/as e investigadores/as es un paso difícil, pero necesario. Desarrollar proyectos de investigación-acción-participación y políticas locales participativas es un paso fundamental para desarrollar una estrategia de barrios saludables políticamente relevante. Keywords: Urban health, Community health, Neighbourhoods and health, Citizen participation, Citizen science, Participatory action research, Empowerment, Palabras clave: Salud urbana, Salud comunitaria, Barrios y salud, Participación ciudadana, Ciencia ciudadana, Investigación-acción-participación, Empoderamiento